A method for adsorbing carbon dioxide

The synthesis of graded porous metal organic framework nanoparticles by microwave and ultrasonic synchronously irradiating and fixing TCPP is solved, and the existing MOFs adsorption problem is small, achieving efficient and environmentally friendly CO2 adsorption effect.

CN115845557BActive Publication Date: 2025-04-18EAST CHINA UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211475950.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-23
Publication Date
2025-04-18
Estimated Expiration
2042-11-23

AI Technical Summary

Technical Problem

The adsorption amount of existing MOFs for adsorbing CO2 is small, and the solvent thermal method has high energy consumption and the solvent is toxic.

Method used

The graded porous metal organic framework nanoparticles were synchronously irradiated by microwave and ultrasonic waves, and tetra-(4-carboxyphenyl)porphyrin (TCPP) was fixed into these nanoparticles to form nanoparticles with continuously adjustable mesoporous channels to improve the adsorption capacity of CO2.

Benefits of technology

It significantly improves the adsorption capacity of CO2 and CO2/N2 selectivity, reduces energy consumption, and uses environmentally friendly water to replace harmful solvents, reducing the cost of regeneration energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115845557B_ABST
    Figure CN115845557B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for adsorbing carbon dioxide, which comprises the following steps: preparing a metal organic framework by synchronous microwave and ultrasonic irradiation, fixing tetrakis (4-carboxyphenyl) porphyrin (TCPP) into the metal organic framework (MOFs), and obtaining hierarchical porous metal organic framework nanoparticles, wherein the hierarchical porous metal organic framework nanoparticles have continuously adjustable mesoporous channels and are fixed with TCPP; S2, adsorbing CO2 by the hierarchical porous metal organic framework nanoparticles 2 According to the method for adsorbing carbon dioxide of the present invention, the micropores of the hierarchical porous metal organic framework nanoparticles can greatly improve the CO 2 The diffusion of molecules in the MOF matrix uses fixed TCPP as the binding center. The Lewis basic nitrogen atoms in TCPP can enhance the CO 2 Chemical adsorption of molecules significantly increases CO 2 Adsorption capacity and CO 2 / N 2 Selective.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to gas adsorption, and more particularly to a method for adsorbing carbon dioxide. Background Art

[0002] Industrial production has caused a large amount of carbon dioxide (CO2) emissions, which has rapidly increased the concentration of CO2 in the atmosphere and exacerbated the greenhouse effect. Therefore, people have conducted a lot of research on carbon capture and storage technology and the removal of trace CO2 from the atmosphere. Porous materials (such as mesoporous silica, carbon-based adsorbents, zeolites and metal-organic frameworks (MOFs)) are currently widely used in CO2 capture due to their advantages such as low regeneration energy, strong adsorption capacity, convenient processing and environmental protection. MOFs are three-dimensional porous crystalline materials composed of metal ions / clusters connected by organic ligands. Methods for synthesizing MOFs include solvothermal, sonochemical, microwave, electrochemical and mechanochemical methods, among which solvothermal is the most common method for synthesizing MOFs. However, the solvothermal method requires heating, has high energy consumption, and the solvents in the synthesis are often toxic. Moreover, the adsorption capacity of known MOFs for adsorbing CO2 is small. Summary of the invention

[0003] In order to solve the problem that the adsorption capacity of CO2 by MOFs in the above-mentioned prior art is relatively small, the present invention provides a method for adsorbing carbon dioxide.

[0004] The method for adsorbing carbon dioxide according to the present invention comprises the following steps: S1, preparing a metal organic framework by synthesizing through microwave and ultrasonic synchronous irradiation, fixing tetrakis(4-carboxyphenyl)porphyrin (TCPP) into a metal organic framework (MOFs), and obtaining hierarchical porous metal organic framework nanoparticles, wherein the hierarchical porous metal organic framework nanoparticles have continuously adjustable mesoporous channels and are fixed with TCPP; S2, selectively adsorbing CO2 through the hierarchical porous metal organic framework nanoparticles.

[0005] Preferably, the mesopore volume of the hierarchical porous metal organic framework nanoparticles is 0.08 m 3 / g.

[0006] Preferably, the hierarchical porous metal organic framework nanoparticles also have micropores. In a preferred embodiment, the micropore volume is 0.34 m 3 / g.

[0007] Preferably, in step S1, TCPP is fixed to the pore walls of hierarchical porous metal-organic framework nanoparticles by a co-assembly one-step synthesis method, and the obtained hierarchical porous metal-organic framework nanoparticles have continuously adjustable mesopore diameters.

[0008] Preferably, in step S1, hierarchical porous metal organic framework nanoparticles are synthesized by microwave and ultrasonic simultaneous irradiation (SMUI). Through the synergistic effect of microwaves and ultrasound, the reaction speed is fast, the yield is higher, the particle shape is uniform, and the phase purity is high. It is an efficient, economical, and environmentally friendly synthesis and processing method.

[0009] Preferably, the SMUI time does not exceed 10 minutes. The hierarchical porous metal organic framework nanoparticles immobilized with TCPP can be synthesized within 10 minutes, which can save a lot of time and cost.

[0010] Preferably, the microwave power is 40-60 watts. In a preferred embodiment, the microwave power is 50 watts.

[0011] Preferably, the ultrasonic power is 80-120 watts. In a preferred embodiment, the ultrasonic power is 100 watts.

[0012] Preferably, in step S1, the block copolymer PEO is used 106 PPO 70 PEO 106 (F127) acts as a template to guide the formation of metal-organic frameworks (Ce-UiO-66MOFs).

[0013] Preferably, the block copolymer F127 is stirred and dissolved in deionized water, sodium perchlorate and acetic acid are added, and ultrasonic dissolution is performed; then ammonium cerium nitrate, 2-aminoterephthalic acid and TCPP are added, and stirred and dispersed; microwave and ultrasonic simultaneous irradiation (SMUI) is performed; after centrifugal separation, washing, activation, and drying, hierarchical porous metal organic framework nanoparticles (CUT) with adjustable mesopore size fixed with TCPP are obtained. In a preferred embodiment, 100 mg of F127 is dissolved in 6 mL of deionized water to form an F127 solution; 0.3 mL of acetic acid and 500 mg of NaClO4·H2O are added and stirred and dispersed; thereafter, 548 mg of ammonium cerium nitrate, 165 mg of 2-aminoterephthalic acid and 12 mg of TCPP are stirred and dispersed in the above solution; then, the solution is transferred to a 25 mL double-necked Pyrex flask for SMUI treatment, and the ultrasonic and microwave sources are turned on in turn, and irradiated under reflux condensation conditions; the mixture is centrifuged to obtain a solid product; then the material is washed with deionized water, N,N-dimethylformamide, and anhydrous ethanol, and the material is immersed in anhydrous ethanol at 60°C for 48 hours, during which the ethanol is continuously replaced to remove all F127 in the pores of the material; finally, the product is vacuum dried at 60°C for 12 hours to obtain the final product CUT.

[0014] Preferably, in step S2, CO2 is adsorbed on the hierarchical porous metal organic framework nanoparticles by physical adsorption.

[0015] Preferably, in step S2, CO2 is adsorbed on the hierarchical porous metal organic framework nanoparticles under pressurized conditions. In a preferred embodiment, CUT has a maximum CO2 adsorption capacity at 1 bar.

[0016] Preferably, in step S2, the hierarchical porous metal organic framework nanoparticles have an improved CO2 selectivity through TCPP. In a preferred embodiment, the CO2 / N2 selectivity is 34.2.

[0017] Preferably, the hierarchical porous metal-organic framework nanoparticles have improved stability by TCPP.

[0018] According to the method for adsorbing carbon dioxide of the present invention, the hierarchical porous metal organic framework nanoparticles are synthesized quickly, greenly and conveniently by synchronous irradiation of microwaves and ultrasonic waves, with low energy consumption and short time. With the help of continuously adjustable mesoporous channels, the micropores of the hierarchical porous metal organic framework nanoparticles can greatly improve the diffusivity of CO2 molecules in the MOF matrix. The fixed TCPP is used as the binding center, and the nitrogen atoms with Lewis basicity in TCPP can enhance the chemical adsorption of CO2 molecules, significantly improving the CO2 adsorption capacity and CO2 / N2 selectivity (i.e., high capacity and selective adsorption can be performed). According to the method for adsorbing carbon dioxide of the present invention, the carbon dioxide adsorption capacity of the hierarchical porous metal organic framework nanoparticles under the conditions of 273K and 1bar reaches 2.53mmol / g, and the CO2 / N2 selectivity can reach 34.2, which provides an effective way to reduce the cost of regeneration energy consumption. In addition, according to the method for adsorbing carbon dioxide of the present invention, the environmentally friendly, safe and economical water is used to replace harmful solvents, which has significant progress. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of the preparation of hierarchical porous metal organic framework nanoparticles according to the present invention.

[0020] Figure 2 1 and 2 are a scanning electron microscope image (a) and a local magnified view (b) of the hierarchical porous metal organic framework nanoparticles according to the present invention.

[0021] Figure 3 1 and 2 are XRD images (a) and a local magnified view (b) of the hierarchical porous metal organic framework nanoparticles according to the present invention.

[0022] Figure 4 FTIR spectrum image (a) and thermogravimetric and differential thermal analysis images (b) of the hierarchical porous metal organic framework nanoparticles according to the present invention.

[0023] Figure 51 and 2 are the N2 adsorption isotherm (a) and the Brunauer-Joyner-Halenda (BJH) pore size distribution diagram (b) of the hierarchical porous metal organic framework nanoparticles according to the present invention.

[0024] Figure 6 The graphs are the CO2 isotherm adsorption curve (a), N2 isotherm adsorption curve (b), CO2 isotherm adsorption heat curve (c) and CO2 / N2 selectivity curve (d) calculated according to the ideal solution adsorption theory of the hierarchical porous metal organic framework nanoparticles at 273K. DETAILED DESCRIPTION

[0025] The preferred embodiments of the present invention are given below in conjunction with the accompanying drawings and described in detail.

[0026] Synthesis of hierarchically porous metal-organic framework nanoparticles with tunable mesopore size immobilized with TCPP

[0027] 100 mg of F127 was dissolved in 6 mL of deionized water to form a F127 solution; 0.3 mL of acetic acid and 500 mg of NaClO4·H2O were added to the above solution and stirred until uniform; then, 548 mg of ammonium cerium nitrate, 165 mg of 2-aminoterephthalic acid and 12 mg of TCPP were stirred and dispersed in the above solution; then, the solution was transferred to a 2.5 mL double-necked Pyrex flask for SMUI treatment, and the ultrasonic and microwave sources (power level: ultrasonic wave is 50 W, microwave is 100 W) were turned on in turn, and irradiated for 10 minutes under reflux condensation conditions; the mixture was centrifuged to obtain a solid product; then the material was washed with deionized water, N,N-dimethylformamide, and anhydrous ethanol, and the material was immersed in anhydrous ethanol at 60°C for 48 hours, during which the ethanol was continuously replaced to remove all F127 in the material pores; finally, the product was vacuum dried at 60°C for 12 hours to obtain the final product CUT, as shown in Figure 1 shown.

[0028] Figure 2 This is a scanning electron microscope image of CUT. It can be seen that the structural morphology of CUT is a fine truncated octahedron, which is consistent with previous reports. At the same time, a large number of open mesopores can be clearly seen on the surface of CUT, which is also consistent with the XRD and BET measurement results.

[0029] Figure 3This is the XRD image of CUT. The crystallinity and peak position of CUT are consistent with the diffraction pattern of UiO-66(Ce) described in the previous literature, verifying the synthesis of UiO-66(Ce). Sharp diffraction peaks appeared in the regions of 2θ of 7.3°, 8.4°, 11.8°, 13.7°, and 14.3°, corresponding to the reflections of (111), (200), (220), (311), and (222) crystal planes, respectively. It is worth mentioning that TCPP has no effect on the crystallinity of CUT because it has the least loading in the material.

[0030] Figure 4 a in the figure is the FTIR spectrum image of CUT, from which the chemical composition of CUT can be determined. -1 and 1650cm -1 The peaks at correspond to the C═O group of the carboxylic acid and the C═N bond of the aromatic ring in TCPP, respectively, proving that TCPP has been successfully attached to the skeleton of CUT.

[0031] Hierarchical porous metal-organic frameworks for CO2 gas adsorption

[0032] The CO2 adsorbent must have sufficient thermal stability to withstand high temperatures. Therefore, thermogravimetric analysis (TG) and differential thermal analysis (DTG) were performed on the CUT in a nitrogen environment, such as Figure 4 As shown in b. The TGA curve of CUT shows that the weight loss is mainly divided into three stages. The first stage of weight loss occurs from room temperature to 100°C, which is caused by the escape of residual ethanol and adsorbed water. The second stage is 200-380°C, mainly due to the removal of acetic acid and the dehydrogenation of Ce oxide clusters. The third stage occurs at 480-650°C, with a weight loss of about 24.5wt%. The skeleton of CUT begins to decompose at 570°C to form CeO2. It is reported that the thermal stability of UiO-66(Zr) is as high as 450°C, and the thermal stability of UiO-66(Ce) is as high as 300°C. Therefore, the higher thermal stability of CUT can be attributed to the presence of TCPP in MOFs.

[0033] The porosity and surface characteristics of CUT were obtained by nitrogen adsorption-desorption test. Figure 5 The N2 adsorption isotherm and BJH pore size distribution of CUT. According to the IUPAC classification, CUT shows type I and type IV nitrogen adsorption isotherms and a narrow H2 type hysteresis loop. The hysteresis loop is generated in the relative pressure range of 0.45-0.9, which indicates that CUT is a mesoporous structure. Table 1 below records the pore structure parameters of CUT and similar UiO-66(Ce).

[0034] Table 1

[0035]

[0036] after, Figure 6 The CO2 adsorption capacity of CUT at 273K and 1 bar was studied. As can be seen from Figures a and b, the CO2 and N2 adsorption capacity of CUT increases with increasing pressure, and CUT has the largest CO2 adsorption capacity (2.53mmol / g) at 1bar. Since CUT has a large number of microporous structures, physical adsorption here is the main mechanism of CO2 capture. At the same time, mesoporous channels also promote the diffusion of CO2 into micropores. Table 2 below shows that CUT has a stronger CO2 adsorption capacity than other Ce-MOFs.

[0037] Table 2

[0038]

[0039] In order to evaluate the interaction strength between CO2 and MOFs in CUT, the isothermal adsorption heat (Qst) of CO2 was determined using the Clausius-Clapeyron equation. Figure 6 As shown in Figure c, the Qst of CO2 adsorption by CUT at zero coverage is 30.15 kJ / mol. Adding TCPP as a co-linker in MOFs improves the interaction between CO2 and MOFs. As the CO2 loading increases, the number of active sites on the adsorbent surface gradually decreases, resulting in a decrease in Qst. Figure 6 The d in the figure is the CO2 / N2 selectivity determined by the ideal adsorption solution theory (IAST). At a CO2 concentration of 15%, CUT has a CO2 / N2 selectivity of 34.2 at 273K and 1 bar, which is significantly higher than similar Ce-MOFs. The enhancement in selectivity may be due to the increase in the Qst value. CUT shows good CO2 selectivity while maintaining a moderate adsorption heat, making it an ideal choice for low regeneration energy consumption materials.

[0040] The above is only a preferred embodiment of the present invention, and is not intended to limit the scope of the present invention. The above embodiment of the present invention can also be modified in various ways. That is, all simple, equivalent changes and modifications made according to the claims and the description of the present invention fall within the scope of protection of the claims of the present invention. The contents not described in detail in the present invention are all conventional technical contents.

Claims

1. A method for adsorbing carbon dioxide, characterized in that: The method comprises the following steps: S1, synthesizing and preparing a metal organic framework by synchronous microwave and ultrasonic irradiation, fixing TCPP into the metal organic framework, and obtaining hierarchical porous metal organic framework nanoparticles, wherein the hierarchical porous metal organic framework nanoparticles have continuously adjustable mesoporous channels and are fixed with TCPP; S2, selective adsorption of CO2 by hierarchical porous metal-organic framework nanoparticles; In step S1, the block copolymer F127 is stirred and dissolved in deionized water, and sodium perchlorate and acetic acid are added and ultrasonically dissolved; then ammonium cerium nitrate, 2-aminoterephthalic acid and TCPP are added and stirred and dispersed; microwave and ultrasonic waves are synchronously irradiated; after centrifugal separation, washing, activation and drying, hierarchical porous metal organic framework nanoparticles with adjustable mesopore size fixed with TCPP are obtained.

2. The method according to claim 1, characterized in that Hierarchical porous metal-organic framework nanoparticles also have microporous channels.

3. The method according to claim 1, characterized in that In step S1, TCPP is fixed to the pore walls of hierarchical porous metal-organic framework nanoparticles through a co-assembly one-step synthesis method, and the obtained hierarchical porous metal-organic framework nanoparticles have continuously adjustable mesopore diameters.

4. The method according to claim 1, characterized in that The time of simultaneous microwave and ultrasonic irradiation shall not exceed 10 minutes.

5. The method according to claim 1, characterized in that The microwave power is 40-60 watts.

6. The method according to claim 1, characterized in that The ultrasonic power is 80-120 watts.

7. The method according to claim 1, characterized in that In step S2, CO2 is adsorbed on the hierarchical porous metal organic framework nanoparticles under pressurized conditions.

Citation Information

Patent Citations

  • Cobalt-nickel double-metal organic framework carbon dioxide adsorption material as well as preparation method and application thereof

    CN110496604A

  • Porphyrin-based covalent organic framework material based on metal ion doping as well as preparation method and application thereof

    CN112920357A